A Case of Diffuse Alveolar Hemorrhage as a Possible Complication of Bivalirudin Therapy - Latt, Htun (Am J Case Rep, 2017)
Patient: Male, 61 Final Diagnosis: Diffuse alveolar hemorrhage Symptoms: Hemoptysis Medication: Bivalirudin Clinical Procedure: Percutaneous coronary intervention Specialty: Cardiology OBJECTIVE: Rare complication/disease BACKGROUND: Diffuse alveolar hemorrhage (DAH) is a rare but potentially fatal complication of anticoagulant or antiplatelet therapy. Bivalirudin is a specific and reversible direct thrombin inhibitor (DTI). CASE REPORT: We report a case of severe DAH, possibly related to bivalirudin use, in a 61-year-old patient undergoing coronary intervention. The patient had presented with an out-of-hospital cardiac arrest due to acute ST elevation myocardial infarction (STEMI). During the coronary intervention, shortly after receiving bivalirudin, the patient started having frank bleeding from the endotracheal tube and developed hemodynamic compromise. Despite aggressive intervention and intensive care, the patient died. CONCLUSIONS: At this time, to our knowledge, there have been no reports of DAH associated with the use of bivalirudin.